L’agriculture itinérante sur brûlis, une menace sur la forêt tropicale humide ? - Serge Bahuchet; Jean-Marie Betsch (Revue d'ethnoécologie)
The attitude of the scientists and managers of development and forest preservation towards the shifting cultivation is very generally ideological. It results in an ambiguous talk based on a homogeneous and out of context image of the term “itinerant agriculture on slash-and-burn field” characterized by fallowing and firing, referred to in English by two not synonymic terms, “Slash-and-burn” that is “to fell and to burn” to cultivate permanently slash-and-burn fields , or “Shifting cultivation” or “Swidden cultivation” which correspond to the French agriculture itinérante or agriculture sur brûlis, that is an agricultural system in which fields are cleared by firing and cropped discontinuously. A persistent use of a fluctuating terminology maintains the ambiguity between clearing by the fire, in a permanent purpose of conversion of the vegetation, and itinerant agriculture, by not taking into account either the variety of the agricultural systems, already underlined by Conklin (1961), or of the itinerance of the fields and thus the interdependence between a short phase of culture and a phase of many years’ fallow. The perception of the agriculture on slash-and-burn field by the majority of agronomists and ecologists is so uniformly negative: archaic, destructive for the forest, unproductive, dangerous even for the future of the planet.Another logical reference, the durability of the practices, must be investigated: in agriculture, the durability must be economically viable, socially acceptable and ecologically solid (Conway 1987) that we can translate by the capacity of an agroecosystem to maintain a stable long-term production based on an ecological, social and economic solidity/validity. (Kleinman et al. 1995).In the context of the announcement of the creation of the National Park of the South of French Guiana, an interdisciplinary program (ecology, pedobiology, ethnology; MNHN-CNRS-IRD) Effects of the traditional cultural practices on soils and forest (French Environment Ministry) studied the effects of the itinerant agriculture on slash-and-burn field from an analysis of the conditions which allow Amerindian communities to satisfy their material and spiritual needs in a forest system.This program set up the following points:– the fine practices of this agriculture, constituting a real strategy, supply efficiently the mineral elements in the cultures, without purchase of fertilizers, and ensure a rapid forest recovery after at least 10 years; the cycles short culture - long fallow allow the self regeneration of an agroforestry system registered since millenniums in the forest dynamics of the river banks;– the adoption of the long fallow limits the spatial extent of every family to 10-15 hectares at most;– the transportation on foot of the harvest towards the village limits the extent of the agriculture to a 3-4 km band from the river; beyond, the forest is protected from an agricultural pressure;– the absence of the market does not lead to an increase of the cultivated surfaces and the pressure on the forest is not increasing thus at present;– the forest of the hinterland includes wide zones restricted by strong social taboos; the conservation of the social organization of the Amerindian ethnic groups is the first condition of the preservation of the forest domain.The real solution for the preservation of the forest heritage in the South of French Guiana, obviously social, was thus already political, before the creation of the “Amazonian Park of Guyana” (2007).